Poslovanje gozdarskih gospodarskih družb v letu 2006 - Furlan, Franci (Gozdarski vestnik, 2007)
Business operations of forestry companies are gradually stabilizing. Total income and profit from sales are increasing. This year the forestry sector is achieving profits again; value added has increased in real terms and exports have grown strongly. The cost of wages and salaries and depreciation have increased in real terms this year, while the number of employees has been significantly reduced.
Keywords: gozdno gospodarstvo; gospodarske združbe; finančno poslovanje; 2006; število zaposlenih